O cérebro eletrônico que me dá socorro: os impactos da Inteligência Artificial Generativa e os usos do ChatGPT na educação - Marchi, Caio Favero (2023)
Generative Artificial Intelligence has increasingly gained prominence in various areas of analysis, and consequently, in perspectives regarding its advancements, uses, and future. Therefore, this research aims to investigate how ChatGPT is being used by students in the fields of Consumer Sciences, Film and Audiovisual, Communication and Advertising, and Information Systems at the Escola Superior de Propaganda e Marketing of São Paulo (ESPM-SP). Additionally, the study aims to understand how the use of these technologies can impact the way this audience learns new content. The results presented here are based on a conclusive, descriptive, and unique cross-sectional research approach. The study draws on an understanding of human learning, an overview of the development of Artificial Intelligence, and its application in the field of education, considering its uses, potential future, and challenges